THE ROLE OF PROSTAGLANDIN (PGE2) IN ALVEOLAR BONE DESTRUCTION - Mohammed, Asam Khalifa (Fakultas Kedokteran Gigi Universitas Jember, 2011)
Inflammation chronic diseases in gingiva and periodontium tissue cause destruction of alveolar bone. Periodontopathy bacteria cause periodontal tissue destruction by host cell activating system, such as prostaglandin. PGE2 induce bone resorption and MMP secretion (Academic report, 1999). Prostaglandin E2 (PGE2) is formed as a result of the metabolism of arachidonic acid. It participates in inflammatory response. Prostaglandin cause alveolar bone destruction by osteoclast activating. Beside it, it enhance calcium metabolism.